Desarrollo del Módulo Complementario para el Sistema de Gestión del Aseguramiento de la Calidad en la Universidad Técnica de Cotopaxi - Christopher Joel, Colcha Gualoto (2024)
Within the framework of the Quality Assurance Directorate at the Technical University of Cotopaxi, a challenge in managing quality indicators has been identified, impacting the efficiency and functionality of various sections of the platform. This technological proposal advocates for a comprehensive solution through the development of a web module, emphasizing the adoption of the agile methodology eXtreme Programming (XP) and leveraging the advanced capabilities of the .NET Framework. The research objective focuses on designing and developing a specialized web module for managing quality indicators. The agile XP methodology will be employed for project management, fostering continuous interaction between users and developers to ensure efficient adaptability to changing requirements and timely delivery of results. Additionally, the specific features of the .NET Framework will be utilized to optimize module development, ensuring a secure and efficient implementation. Results from the module's implementation will reflect substantial improvements in each area of indicator management, underscoring the effectiveness of the agile methodology and applied advanced technologies. The implementation of the web module enhanced sections, enabling them to manage entered data in a more specific way.